Deteksi dan Identifikasi Fitoplasma yang Berasosiasi dengan Penyakit Layu Kelapa Di Pulau Derawan, Kalimantan Timur - Prasetyo, Agus Eko; Mutaqin, Kikin Hamzah; Giyanto, Giyanto (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2017)
Coconut is a major commodity in Derawan island as source of additional income for the farmers. Research was conducted to detect and identify phytoplasmas associated with coconut wilt disease in Derawan island. Coconut wilt disease was indicated by the typical symptoms, i.e. leaf yellowing, shorten of coconut sheaths and leaves, necrosis and collapse of old leaves, and also nut fall. The presence of phytoplasmas in phloem tissues of coconut stem was observed using fluorescence and electron microscope. Identification of phytoplasmas was carried out by nested-PCR and sequencing of the 16S rRNA gene. DNA fragment of phytoplasma with the size of 1.25 kbp was successfully amplified using primer pairs P1/P7, followed by primer pairs R16F2n/R16R2. Sequence analysis of the amplified fragments showed that phytoplasma associated with coconut wilt disease in Derawan island belongs to 16SrII (witches broom phytoplasma) and 16SrXI (ca. Phytoplasma oryzae) groups.